Accountability of Performance Integrated With The Value of Islamic Civilization: The Case Of Muhammadiyah University of Makassar - Wa Ode Rayyani; Ahmad Abbas (The Pontianak State Institute of Islamic Studies, 2021)
The objective of this research is to describe accountability of performance integrated with the value of Islamic civilization and find the essence from framework of Islamic accountability of organization. This research is qualitative type using interpretive spiritualism paradigm under ethnomethodology approach. The object of this research is Muhammadiyah University of Makassar and the informants are people involved in making a decision in the university. The result reveals that theaccountability in Muhammadiyah University of Makassar is built using the religious spiritualism under a foundation of Islamic values consisting ofukhuwah and sincerity, amanah, oriented goal, effectiveness and efficiency, opennes, and consistency. The further result discloses that sincerity isthe strongestvalueto build the accountability ofperformance